Caffeine as an Ergogenic Aid: A Literature Review of Mechanisms of Action, Performance Effects and Safety Thresholds - Urszula, Justyna Wojciechowska; Adam Rafałowicz; Izabela Zajkowska (Quality in Sport, 2025)
Abstract